Ammonium oxalate as a masking agent for the complexometric determination of manganese(II) - Perdur, Nagaraj; Nellikalaya, Gopalakrishna Bhat; Gopalakrishnayya, Chandrashekara Kalchar (Vietnam Journal of Chemistry, 2015)
A simple, rapid and accurate complexometric method for the determination of manganese in the presence of other metal ions is described, based on the selective masking ability of ammonium oxalate towards Mn(II). Manganese(II) along with other associated metal ions present in a given sample solution is first complexed with an excess of EDTA and the surplus EDTA is titrated with zinc sulphate solution at pH 5-6 (Hexamine buffer) using xylenol orange as indicator. A known excess of 5% aqueous solution of ammonium oxalate is then added to displace EDTA from Mn(II)-EDTA complex and swirled well. The released EDTA is again titrated with zinc sulphate solution as before. The method works well in the range 2.19-21.96 mg of manganese(II) with the relative error ± 0.46% and standard deviation ≤ 0.03 mg. The effect of the presence of various diverse ions on the accuracy of the results has been studied. The method has been satisfactorily applied for the determination of manganese in alloys.